The Effect of Virtual Reality (VR) Learning Media on Enhancing Critical Thinking Skills in Science Subjects among 4th Grade Students at an Integrated Islamic Elementary School - Absor, Ulil; Atikoh, Nur; Arifuddin, Ahmad (Indonesian Journal of Elementary Education and Teaching Innovation, 2025)
Due to repetitive, teacher-centered education, which makes students passive and less involved in the learning process, SDIT Al-Ishlah Sudimampir students' critical thinking abilities in scientific classes are low.  Virtual reality (VR) media is thought to be able to offer a stimulating educational experience and can improve 21st-century abilities, especially critical thinking.  This study intends to: (1) investigate the use of Virtual Reality (VR) learning materials in Natural Science (IPA) courses for fourth-grade students at SDIT Al-Ishlah Sudimampir; (2) evaluate the enhancement of critical thinking abilities among fourth-grade science learners following the use of VR-based learning materials; and (3) ascertain if employing VR learning materials has a greater influence on fourth-grade pupils at SDIT Al-Ishlah Sudimampir than using traditional media (PowerPoint). This study used a Nonequivalent Control Group Design using a quantitative methodology. 52 students made up the sample, which was split into two groups: a control group (25 students using PowerPoint) and an experimental group (27 students using VR). Pre-tests, post-tests, and observation sheets were used to gather data, which were then analyzed using both descriptive and inferential statistical techniques. The study's findings demonstrate that: (1) the use of virtual reality learning materials was effective, as demonstrated by observational data showing that student participation in the experimental class and the learning implementation both achieved an exceptional category (100%); (2) After using VR learning materials, students' critical thinking abilities significantly improved, as evidenced by the experimental group's average pre-test score of 51.85, which rose to 86.67 in the post-test; and (3) the Independent Samples T-test showed a significant difference between the two groups, with a Sig. (2-tailed) value of 0.000 (< 0.05). The experimental group's average N-Gain score was 0.756 (high category), which was significantly higher than the control group's 0.519 (medium category). These results showed that the learning medium had a substantial impact on students' critical thinking abilities, leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (H₁). Thus, it can be said that using Virtual Reality (VR) learning materials significantly improves students' capacity for critical thought.